2018
DOI: 10.1186/s12958-018-0358-6
|View full text |Cite
|
Sign up to set email alerts
|

The enigmatic seminal plasma: a proteomics insight from ejaculation to fertilization

Abstract: BackgroundThe ‘omics’ approach for a noninvasive diagnosis of male reproductive system disorders has gained momentum during the last decade, particularly from a screening and prognosis point of view. Due to the rapid development in assisted reproductive technologies (ART) over the years, the major focus of proteomic studies has been around the ejaculated spermatozoa. Although seminal plasma is not a requirement for ART, the question arose whether the role of seminal plasma is merely to transport spermatozoa.Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
107
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 96 publications
1
107
0
5
Order By: Relevance
“…In a previous study, we demonstrated the different expressions of testicular phosphorylated proteins in the between T1DM and T2DM mouse model (Sampannang et al, in press). Since the proteomics of ejaculated seminal plasma have been revealed (Samanta, Parida, Dias, & Agarwal, 2018), the seminal secretion may contain some phosphorylated proteins and their expressions may be different between DM types. Since the proteomics of ejaculated seminal plasma have been revealed (Samanta, Parida, Dias, & Agarwal, 2018), the seminal secretion may contain some phosphorylated proteins and their expressions may be different between DM types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we demonstrated the different expressions of testicular phosphorylated proteins in the between T1DM and T2DM mouse model (Sampannang et al, in press). Since the proteomics of ejaculated seminal plasma have been revealed (Samanta, Parida, Dias, & Agarwal, 2018), the seminal secretion may contain some phosphorylated proteins and their expressions may be different between DM types. Since the proteomics of ejaculated seminal plasma have been revealed (Samanta, Parida, Dias, & Agarwal, 2018), the seminal secretion may contain some phosphorylated proteins and their expressions may be different between DM types.…”
Section: Introductionmentioning
confidence: 99%
“…Seminal plasma produced from the male reproductive tract, especially in seminal vesicles that secrete essential factors and proteins, is involved in sperm motility, capacitation and acrosome exocytosis. Since the proteomics of ejaculated seminal plasma have been revealed (Samanta, Parida, Dias, & Agarwal, 2018), the seminal secretion may contain some phosphorylated proteins and their expressions may be different between DM types. To provide the best of our knowledge, the association between seminal secreting substances and low-seminal plasma quality of male subfertility caused by DMs needs to be more explained.…”
Section: Introductionmentioning
confidence: 99%
“…Seminal plasma is a very complex fluid composed of secretions from testis and male genital tract. In addition to previous biochemical studies, proteomic approaches allowed the identification of numerous seminal plasma proteins in the chicken and mammalian species (Atikuzzaman et al, ; Borziak, Álvarez‐Fernández, Karr, Pizzari, & Dorus, ; Brito et al, ; Camargo, Intasqui, & Bertolla, ; Druart et al, ; Intasqui et al, ; Labas et al, ; Perez‐Patino et al, ; Samanta, Parida, Dias, & Agarwal, ). Proteomics profiles reflect sperm functional traits (Intasqui et al, ) and highly differ between species.…”
Section: Introductionmentioning
confidence: 99%
“…During ejaculation, efferent ducts and accessory sex glands add immune components and extracellular microvesicles such as epididymosomes and prostasomes to the spermatozoa (Jodar, Soler‐Ventura, Oliva, & Molecular Biology of Reproduction and Development Research Group, ). These secretory molecules regulate sperm function (Shilpa et al, ) and subsequent fertilization events in the female reproductive tract (Samanta, Parida, Dias, & Agarwal, ; Sullivan & Saez, ). Comparatively, the mechanisms of systemic immune tolerance towards male germ cell antigens as well as those that maintain immune privilege remain to be resolved.…”
Section: Testicular Immune Mechanismmentioning
confidence: 99%